2012
DOI: 10.1111/j.1758-5872.2012.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of suicide attempts in schizophrenia and major depressive disorder: An exploratory study

Abstract: Suicide attempts in schizophrenia and MDD have similar features, with quite a few notable differences, which have been discussed at length in the present paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…In the Indian context, 34% of patients with schizophrenia reported at least one suicide attempt in a hospital based cross sectional study from Ahmadabad with 50 outpatients each of schizophrenia and major depressive disorder (Banwari et al, 2013). A study from Mumbai reported that out of 200, 38% (n =76) reported at least one severe suicide attempt, and 9.5% (n = 19) had attempted suicide more than three times (Shrivastava et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the Indian context, 34% of patients with schizophrenia reported at least one suicide attempt in a hospital based cross sectional study from Ahmadabad with 50 outpatients each of schizophrenia and major depressive disorder (Banwari et al, 2013). A study from Mumbai reported that out of 200, 38% (n =76) reported at least one severe suicide attempt, and 9.5% (n = 19) had attempted suicide more than three times (Shrivastava et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the presence of an adjustment disorder was more frequent in impulsive SAs than in planned SAs. Because impulsive SAs often experience stressful events prior to a suicide attempt 10 , 34) and because adjustment disorder can be defined as the experience of emotional and behavioral problems in response to identifiable stressors, 35) the present findings are plausible.…”
Section: Discussionmentioning
confidence: 67%
“…Suicide attempters with high intent – according to a study including 203 patients – are less likely to be married, more likely to be male, have a diagnosis of major depressive disorder (MDD) and experience a higher number of recent life events in the month preceding the attempt (Kumar et al, 2006). According to Banwari et al (2013) suicide attempts in MDD and schizophrenia patients share common features but schizophrenia patients show a significantly higher intent to die, compared with MDD patients (Banwari et al, 2013). According to a study by Stefansson et al (2015), intent to die and violence both contribute to the risk of suicide but are not correlated with each other and therefore confer two different components of the suicide risk.…”
Section: Question Of Intent and Violent Suicidementioning
confidence: 99%